Atrial septostomy to prevent pulmonary hypertension crisis in children with ventricular septal defect (VSD) and pulmonary hypertension (PH) underwent cardiac surgery: a case series - Haryo Aribowo; Yoga Arditya; Gita Christy Gabriela (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2023)
Severe pulmonary hypertension (PH) was reported in 22.4% of ventricular septal defect (VSD) and it was mainly seen on a large VSD. Atrial septostomy (AS) could improve the hemodynamic condition and long-term survival of PH patients. Here, three VSD and PH cases in children who underwent AS surgery as their early treatment, concomitant with PH-specific pharmacological treatment were reported. Patient’s hemodynamic and general condition improved with no further complications during the follow-up period. Atrial septostomy was usually conducted after all PH-specific pharmacological interventions failed. However, a study found that the survival benefit of AS was significantly increased if it was conducted before PH-specific pharmacotherapies. Most of the patients in this case received immediate hemodynamic and functional improvement. In this case series, it was reported that the AS procedure could lower the pulmonary arterial pressure and be safely conducted without further complications or death >24 hr post-surgery. Considering the clinical benefit, safety procedure, and improved pulmonary arterial pressure, performing AS procedure concomitant with PH-specific pharmacotherapy as an early treatment for PH patients is recommended.